The Effect of Spread Spectrum Modulation on Power Line Communications - Ercan, Seda Ustun; Pena-Quintal, Angel; Thomas, Dave (MDPI, 2023)
Interference in Power Line Communication (PLC) is examined in this paper. PLC is a wired communication technology that provides communication and data transmission over the existing electrical network. It uses the electrical wiring in buildings or the electrical grid to transmit data signals between devices, rather than using dedicated communication cables or wireless signals. Many applications employ PLC technologies, which have the benefit of leveraging existing power connections for both power and data transfer, reducing cost and complexity. These interactions may be observed in contemporary smart grids and automobile power networks, where lengthy cables, switching power supplies and communication links all work together but exacerbate Electromagnetic Interference (EMI) problems. This research examines the effects of spread spectrum methods used to reduce EMI from power converters on PLC systems. Spread Spectrum Modulation (SSM) and its three variants, Sine, Random and Sawtooth, are frequently employed to meet the requirements of electromagnetic compatibility, however, there are some repercussions that may be detrimental to the converter or the rest of the electrical network. These outcomes occur for various modulation algorithm settings and at various frequencies. Measurements are made utilising the Frame Error Rate (FER) value provided by the PLC link system to ascertain the interference produced by a Silicon Carbide (SiC)-based DC-DC converter in order to investigate these concerns and standardise an assessment approach. To examine the effect of SSM on reducing EMI in the frequency domain, the peak index of a CISPR-16 EMI receiver is used.
Ustun Ercan, Seda/0000-0002-8688-5852; Thomas, David/0000-0002-1815-8477; Pena Quintal, Angel Eduardo/0000-0002-4672-0260;
Keywords: Power Line Communication; Modulation; Spread Spectrum; DC-DC Converter; EMI Mitigation